BENEFÍCIO DE PRESTAÇÃO CONTINUADA E O DIREITO À ASSISTÊNCIA SOCIAL: legitimidade dos condicionantes de concessão do BPC ao idoso e ao deficiente em Teresina (PI) - Amaral, Maria Fernanda Brito do (2014)
This thesis was the object of investigation Continued Benefit - BPC elderly and disabled established by Articles 203 and 204 of the Federal Constitution and regulated by Law No. 8,742 / 93, Organic Law of Social Assistance. His goal was to analyze the dynamics of the BPC in Teresina-Pi having as goal the legitimacy of their conditioning defined in Law 8742/93 front to fundamental social rights and principles of citizenship and human dignity contained in the Magna Carta. The method used in the research was the historical-dialectical, with an as-qualitative approach, the main instrument of data collection questionnaire with open and closed questions. The research subjects were 30 beneficiaries, potential beneficiaries 30 or who had denied the benefit, and the benefit 24operadores, all in Teresina-PI. Quantitative data were subjected to statistical program SPSS and discourse analysis for open and qualitative issues. Empirical data demonstrate a lot of elderly and disabled who denied benefits; not the legitimacy of all the subjects to grant requirements, in particular, the per capita income of less than ¼ of the minimum wage; existence of problems in implementing the benefit of the disagreement even be done in INSS, the expansion of functions outside the scope of an insurer, the work that candidates give in attendance by lack of education, ignorance and non-adherence to the logic of benefit rights , among others. We conclude that the BPC coexists with a crisis of legitimacy for the controversy that has been promoting for the disagreement of experts on the subject, the positions of patriotic courts, not by the acceptance criteria for beneficiaries and potential beneficiary, the lag in the criteria for measuring poverty in relation to other government programs and services, among others. Anyway, legality does not mean legitimacy, especially when not meet the needs and demands of your target audience.